Biofortified bean genotypes under integrated soil fertility management across sub-humid agroecological zones of the Democratic Republic of Congo - Antoine, Kanyenga L.; Roger, Kizungu V.; Emery, Kasongo L.; Adrien, Kalonji M.; Chirwa, Rowland M. (Academic Journals, 2020)
This study was implemented to evaluate the performance of biofortified bean under different integrated soil fertility management (ISFM) options and agro-ecological conditions in Democratic Republic of Congo (DRC). A Split-plot design with eight genotypes as main factors and four ISFM options as secondary factors was carried out in eight production zones distributed across South-Kivu, North-Kivu, and Katanga provinces. The application of lime + manure + NPK increased the bean yield by 173% in Lohutu. Compared to local variety in Lohutu, the CODMLB001 variety under the same option increased the yield by 252%. The same ISFM option allowed best response in terms of micronutrient content of bean in Rutshuru, inducing up to 80.3 mg.kg-1 Fe, representing increase 41%. For Zn, the best response was obtained with lime + NPK applied in Kipopo that induced up to 32.2 mg.kg-1 Zn. Lime + manure + NPK fertilizer option reduced root rot severity by 17.8% compared to the control. This study confirmed the potential of increasing bean productivity, micronutrient and reducing the severity of major diseases through application of soil fertility management options, which will vary with the bean genotype and the environment under which bean is cultivated.